Papuan Tabla Language Preservation Strategy - Iskandarsyah Siregar (Britain International for Academic Research (BIAR-Publisher), 2022)
The Papuan Tabla language is as an endangered language. In that language, knowledge is recorded as local identity. This discussion aims to find ways to increase the vitality of the Papuan Tabla language and literature. The method used is literature and field studies through surveys, observations, interviews, documentation, and learning. As a result, in increasing the vitality of the Papuan Tabla language and literature, the language and literature must be researched, documented, and revitalized. Linguists have researched the Papuan Tabla language system. The recording of language in various spheres of life needs to be documented. Language and literature learning is designed in the form of community or family-based revitalization. The three activities received support from the Tabla Papuan community and stakeholders. With this support, Tabla Papua's language and literature can increase its life force, primarily when people use it in the family realm. In conclusion, preservation in the form of research, documentation and revitalization of the Papuan Tabla language and literature can increase the vitality of language and literature. The program can be one of the models in saving languages from extinction.